1988
DOI: 10.1161/01.cir.78.6.1449
|View full text |Cite
|
Sign up to set email alerts
|

Complement and neutrophil activation in the pathogenesis of ischemic myocardial injury.

Abstract: Complement depletion with cobra venom factor (CVF) before coronary artery ligation has been previously shown to reduce subsequent ischemic myocardial tissue injury in the baboon; however, whether complement depletion after the initiation of acute myocardial ischemia affords similar myocardial preservation is not known. Both complement depletion with CVF or the administration of certain nonsteroidal anti-inflammatory drugs, including ibuprofen, are thought to decrease myocardial infarct size by reducing polymor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
68
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(73 citation statements)
references
References 24 publications
5
68
0
Order By: Relevance
“…Infiltration of the heart by PMNs is an important cause of myocardial damage in the setting of ischemia/reperfusion (47)(48)(49)(50)(51)(52)(53). Consistent with this view, histologic examination of the vasculature from a heart preserved in LR, which subsequently failed, showed a ring of PMNs adherent to the vessel surface, which was not seen in a successfully transplanted cardiac graft preserved in LR + db-cAMP (Fig.…”
Section: Resultsmentioning
confidence: 56%
“…Infiltration of the heart by PMNs is an important cause of myocardial damage in the setting of ischemia/reperfusion (47)(48)(49)(50)(51)(52)(53). Consistent with this view, histologic examination of the vasculature from a heart preserved in LR, which subsequently failed, showed a ring of PMNs adherent to the vessel surface, which was not seen in a successfully transplanted cardiac graft preserved in LR + db-cAMP (Fig.…”
Section: Resultsmentioning
confidence: 56%
“…Finally, complement activation may additionally be driven by other processes such as reperfusion events [42][43][44][45] or liberation of intracellular complement activators from the cells. 46,47 A major unanswered question relates to the problem of why the terminal complement sequence should assume such a central role in atherogenesis. It is possible that C5b-9 attack on nucleated cells occurs at some stage, accentuating proin- Immunostaining of aortic cross sections using a monoclonal antibody directed against rabbit C5b-9.…”
Section: Discussionmentioning
confidence: 99%
“…Organ ischemia induces immediate cellular injury that is significantly magnified by the return of blood flow and can lead to a systemic inflammatory response that damages remote organs as well (1). Due to the sensitivity of the mucosal surfaces, ischemia/reperfusion (I/R) 3 -induced injury is exceptionally prominent in the intestine and is frequently followed by liver and lung damage (2).…”
mentioning
confidence: 99%
“…Mesenteric I/R-induced tissue injury is mediated by at least two components, neutrophil infiltration and complement activation (3)(4)(5). Initial studies showed protection from I/R-induced injury after neutrophil depletion (4,5).…”
mentioning
confidence: 99%